1999
DOI: 10.2307/1387606
|View full text |Cite
|
Sign up to set email alerts
|

The National Congregations Study: Background, Methods, and Selected Results

Abstract: The Nation4l Congregations Study (NCS) was ";ndUcted in~njunclion~ith the 1998 Ge~ral~~ial Survey (GSS). The 1998 GSS as/ud respondenl8 woo altend religious. s~rvr.ces 10 na~the" rel,lI'ous congregation, thus generating a nationally representative sampk of rel'gwUB congregat'o~.. Data about these congregaRoIUI wen collecud uia a one-hour interuuw with. OM key znformanta ffll1Uster. pru:st. rabbi, or other staff person or kcukrfrom 1236 congregations. Information w~g ather:d aJJ:>utmul~pk aspecl8 of congregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(143 citation statements)
references
References 33 publications
4
135
0
1
Order By: Relevance
“…Chaves et al (1999) discuss the validity and reliability of relying on a single key informant to report church characteristics. Such persons are likely to over-estimate the extent to which their views correspond to their congregation's views.…”
Section: Notesmentioning
confidence: 99%
“…Chaves et al (1999) discuss the validity and reliability of relying on a single key informant to report church characteristics. Such persons are likely to over-estimate the extent to which their views correspond to their congregation's views.…”
Section: Notesmentioning
confidence: 99%
“…The GSS is a representative sample of the noninstitutionalized adult population in the United States. If a GSS respondent indicates he or she attends religious services once a year or more, the GSS asks for the name of the congregation, which then forms a nationally representative sample of congregations (Chaves 2007;Chaves et al 1999). The NCS was conducted in 1998, 2006, and 2012 and gathered a representative snapshot of congregations in the United States by interviewing a key informant from the congregation nominated in the GSS, most often the senior pastor.…”
Section: Methodsmentioning
confidence: 99%
“…(Chaves et al 1999) To generate the pastoral leaders sample, all persons who indicated they attended religious services were extracted from the random sample of individuals who participated in the 1998 General Social Survey conducted by the National Opinion Research Center (NORC). These church attendees were then asked to provide information on the religious organization to which they belonged.…”
Section: Methodsmentioning
confidence: 99%